The impact of government subsidies on industrial management: the Israeli experience. - Finger, Nachum (New York: Praeger Publishers, 1971)
The book examines the impact of government subsidies on three major management decision areas :the financial area,the plant location,and the choice technology.
Bibliography: p. 95-100.
obn 25/01/2019
Loans
Keywords: Subsidies; Industrial management